(untitled) (CAHIERS MAGELLANES-NS, 2024)
The usage of electric mobility is expected from the developing countries to reduce the carbon emission. The major pollution is in urban mobility and which drastically required to be controlled for sustainable and reliable option for the electric mobility. The major options go to the renewable sources and hence the paper gives the various solutions to adopt in the urban e-mobility to make the higher reliable system. This paper gives also the reliability ration with respect to the available resources. The work represents and predicts the possible solutions to make the urban e-mobility with highly sustainable and reliable to make the city life healthier and safer.